THE ROLE OF DIGITAL TRANSFORMATION AND RISK-BASED APPROACHES IN ENHANCING THE EFFICIENCY OF PUBLIC BUDGET EXPENDITURE CONTROL (Global Conference on Multidisciplinary Research and Innovation, 2026)
In the context of the modern economy, ensuring the efficiency of public budget expenditures has become one of the priority directions of public administration. In particular, improving mechanisms for controlling the targeted use of budget funds is crucial for ensuring economic stability, the rational use of state resources, and enhancing the effectiveness of social programs. In recent years, digital transformation processes in public financial management have been developing rapidly on a global scale, shaping new approaches to budget control.